CHEMTAX determination of Southern Ocean phytoplankton distribution and adaption: An observational and experimental study assessing the co-limitation of Light, Iron and other Trace Metals on phytoplankton productivity and community composition. - Viljoen, Johannes Jacobus (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.